South Gaulish terra sigillata in Ammaia (São Salvador de Aramenha, Marvão): typological and stratigraphical analysis - Quaresma, José Carlos (2021)
This article summarizes our work on the imports of South Gaulish terra sigillata from the town of Ammaia, in the southern part of the province of Lusitania and within the geo-sphere of the provincial capital, Augusta Emerita. The assemblage available was fully studied: it includes the assemblages from the excavations of the early 20th century, the excavations of the years 1990 and 2000, as well as the sets of excavations of the RadioPast Project (2008-2011). The subject is analysed with regard to its typological concerns, but mainly with respect to its stratigraphical evolution: Ammaia presents excellent levels from Claudian-Neronian, Flavian, Flavian-Antonine eras and finally between AD 125-150. The empirical data from the first and last stages are particularly important, given the scarcity of stratigraphical information across the Iberian Peninsula, especially concerning the Julian-Claudian period.